5PSQ-123 Failure modes, effects and criticality analysis: application to a hospital pharmacy. (March 2019) - El Wartiti, MA; Enneffah, W; Cheikh, A; Abouatia, M; Lamsaouri, J; Taoufik, J; Bennana, A
Abstract : Background: The pharmacy is the last link in the drug chain and error, which is never an isolated fact, is still a troublesome reality. Everything must be organised to minimise risks and their severity. As such, Failure Modes, Effects and Criticality Analysis (FMECA) applied to the pharmaceutical activity helps control the risks of non-compliance that can negatively affect the quality of provided services. Purpose: The objective of this work was to apply in practice the FMECA tool (example of the procedure of medical devices' reception) at a hospital pharmacy engaged in the process of implementing a quality management system, in order to propose for each risk identified and analysed, a matrix of preventive and corrective actions. Material and methods: Our work took place in three stages: Identification and description of elementary processes forming the macro–process of medical devices' reception at our hospital's pharmacy pole. Drafting the procedure describing the main activities forming the macro–process in question. Application of the FMECA tool to the described activities in order to identify different risks and calculate their criticality (criticality=frequency × severity). Results: The results of this risk analysis, applied to the macro-process of medical devices' reception at our hospital's pharmacy pole, allowed us to identify 13 risks (among which three had a criticality score ≥8), to reconsider certain practices and to propose matrices of measurements for taking charge of most critical risks. Conclusion: This experience helped to sensitise staff to the 'risk culture'. In addition, the results specific to our hospital's pharmacy pole may constitute a model available to other hospital pharmacies seeking to improve the quality of their services, which would help to upgrade the profession of hospital pharmacists. References and/or acknowledgements: None. No conflict of interest.